2021
DOI: 10.1002/elsa.202100175
|View full text |Cite
|
Sign up to set email alerts
|

Cathodic corrosion of Au in aqueous methanolic alkali metal hydroxide electrolytes: Notable role of water

Abstract: Cathodic corrosion is an electrochemical process that induces restructuring, roughening, and etching of metal surfaces at a highly negative surface charge density, yet, details of the reaction mechanism are not fully resolved. An in‐depth fundamental understanding of the processes and parameters underlying cathodic corrosion is crucial for tailoring the surface structure of the metal electrodes and for synthesizing shape‐ and size‐controlled nanoparticles. Here, we investigate the relevance of water and hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Moreover, the current in these voltammetric profiles is normalized to the electrochemically active surface area (EASA). The EASA has been estimated by equating the double‐layer capacity of the anodically polarized and as‐polished Cu electrodes at −0.10 V vs. RHE, where neither Faraday reactions nor adsorption processes occur [30,55–57] . Generally, for Cu electrodes, the peaks observed in the regime between 0.2 V and 0.4 V vs. RHE can be ascribed to the formation and reduction of Cu 2 O [58] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the current in these voltammetric profiles is normalized to the electrochemically active surface area (EASA). The EASA has been estimated by equating the double‐layer capacity of the anodically polarized and as‐polished Cu electrodes at −0.10 V vs. RHE, where neither Faraday reactions nor adsorption processes occur [30,55–57] . Generally, for Cu electrodes, the peaks observed in the regime between 0.2 V and 0.4 V vs. RHE can be ascribed to the formation and reduction of Cu 2 O [58] .…”
Section: Resultsmentioning
confidence: 99%
“…The EASA has been estimated by equating the double-layer capacity of the anodically polarized and as-polished Cu electrodes at À 0.10 V vs. RHE, where neither Faraday reactions nor adsorption processes occur. [30,[55][56][57] Generally, for Cu electrodes, the peaks observed in the regime between 0.2 V and 0.4 V vs. RHE can be ascribed to the formation and reduction of Cu 2 O. [58] The peaks at potentials below 0.2 V can be attributed to OH adsorption and desorption on different low-index surface facets.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…[49,50] The presence of water, even at low concentrations, might trigger cathodic corrosion of Au(111) at potentials negative to the hydrogen evolution regime and consequently induces prominent structural changes. [37,51] Thus, we have investigated the electrochemical behavior of Au(111) in MPPip-TFSI and BMP-TFSI at potential regimes, where both the electrolyte and working electrode are stable.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…Cathodic corrosion is an electrochemical etching process that restructures and possibly dissolves metal surfaces upon polarization at sufficiently negative potentials in the presence of non-reducible cations. 18,[24][25][26][27] It is demonstrated that metal corrosion under cathodic polarization can arise in a range of conditions, from mild (at pH 7 and E = −1 V vs. SHE) to extremely harsh conditions (such as in a 10 M NaOH or KOH electrolyte and E < −5 V vs. SHE). 19,[28][29][30][31][32] For instance, Pt dissolution at moderate negative potentials during ORR in water and organic media was observed.…”
Section: Introductionmentioning
confidence: 99%
“…), the polarization time, the applied electrode potential, and the electrochemical properties of the metal itself. 16,18,19,26,33 Normally, the restructuring of metal surfaces can have a significant impact on its kinetics, intrinsic activity and selectivity, stability, and reaction mechanisms in (electro) catalysis. 20,25,34,35 Thus, cathodic corrosion can also be beneficially applied to tailor the surface structure of an electrocatalyst, thereby unveiling sites with favorable catalytic properties.…”
Section: Introductionmentioning
confidence: 99%